2013
DOI: 10.1177/1071100713484300
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Controlled Trial of Plantar Versus Dorsal Incisions for Operative Treatment of Primary Morton’s Neuroma

Abstract: Level I, prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 22 publications
1
29
2
3
Order By: Relevance
“…18,47 These findings do not quite correlate with the low rate of scar-related problems (5.3%) in our series. In agreement with Karges, 19 the authors believe that hypertrophic scar formation may be avoided by slightly everting wound closure.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…18,47 These findings do not quite correlate with the low rate of scar-related problems (5.3%) in our series. In agreement with Karges, 19 the authors believe that hypertrophic scar formation may be avoided by slightly everting wound closure.…”
Section: Discussioncontrasting
confidence: 69%
“…This does not match with previous studies, where the rate of scar-related problems was 15% to 27%. 18,42,47 This single-surgeon case series using a longitudinal plantar approach with standardized diagnostic examination, operative procedure, postoperative schedule, follow-up protocol, and histological confirmation in all cases may have the limitation of lacking a control group with dorsal approach. Furthermore, there could be a bias because the treating surgeon also did the follow-up examination.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a meta-analysis presented by Glasoe and Coughlin [31], the majority of authors recommend plantar approach rather than dorsal approach. On the other hand, in a trial comparing plantar and dorsal neurectomies, Akermerk et al found showed no differences in the results, but different types of complications [34]. In the current study, in order to avoid scars on the plantar side, the dorsal approach was used as recommended by Mann and Reynolds [35].…”
Section: Discussionmentioning
confidence: 65%
“…Arcuatum oder Lig. Sie reichen von 5 cm (Amadio und Beckenbaugh (1986); Doyle und Botte (2003); Green und Rayan (1999)) bis 12 cm distal des medialen Epicondylus (Siemionov et al 2007 Sonderformen sind lagerungsbedingte Schäden nach Narkosen oder bei chronisch Bettlägerigen (Sunderland 1978). Flexor-Pronator-Aponeurose mit variablen Bändern.…”
Section: Aaem American Association Of Electrodiagnostic Medicine (2002)unclassified
“…Eine prospektive randomisierte kontrollierte Studie verglich den dorsalen mit dem plantaren Zugang (Akermark et al 2013). Interdigitalnerv betroffen -Hypästhesie der angrenzenden Zehenhälften häufig, jedoch nicht obligat Neurografischer Befund -Sensible Neurografie technisch aufwendig Bildgebung -Im Sonogramm und mittels MRT Nachweis des Morton-Neurom's sowie anderweitiger raumfordernder Prozesse .…”
Section: Anamneseunclassified